До питання відкриття склепу гетьмана України Кирила Розумовського (на основі матеріалів ЦДАВО м. Київ) - Оксінь, Т. (Сiверянський лiтопис, 2018)
Підготовлено до друку архівний документ – лист Федора Ернста до Українського
головного управління науковими установами при Народному комісаріаті освіти УСРР
(далі Укрнаука) 1927 р. про відкриття склепу Кирила Розумовського у Воскресенській
церкві м. Батурин із фондів Центрального державного архіву вищих органів влади та
управління України (далі ЦДАВО). Подготовка к печати архивного документа – письма Федора Эрнста в Украинское
управление научными учреждениями при Народном комиссариате просвещения УССР
(далее Укрпросвет) 1927 об открытии склепа Кирилла Разумовского в Воскресенской
церкви г. Батурин из фондов центрального государственного архива высших органов
власти и управления Украины (дальше ЦГАВО). Preparation for the publication of archival document – Fedor Ernst`s letter to the Ukrainian
Main Department of Scientific Institutions under the Public Commissariat of Education of
Ukrainian SSR (hereinafter UKR science) in 1927 about the opening of Kirill Razumovsky`s
vault in the Resurrection Church, Baturyn from the funds of the State Archive of Supreme
Authorities of Ukraine (hereinafter SASA).
The purpose of the article is a disclosure of an unknown page of the history related to Ukrainian
Hetman Kyrylo Rozumovski, namely the consequences of opening his crypt. In the funds
CSASBPGU was found a document which describes the opening of Hetman Kyrylo Rozumovsky’s
crypt in the city of Baturyn, June 1927. The question of opening Kyrylo Rozumovsky’s burial is
still poorly studied. The only thing was known that Oleh Poplavski – curator of Konotop Museum
without any permit, opened the crypt of Hetman. For a long time, it remains unknown to
the public whether he had permission to do it, did he follow the procedure, what was done and
found, and what was the reaction of his superiors and the residents of Baturyn. Fedir Ernest’s
letter rises the curtain in this question. It becomes clear that catching up with the events Oleg
Poplavski in the next couple days makes a protocol, does appropriate measurements (temperature,
humidity, the description of the coffin remains) and invites a photographer. In addition to it, he
breaks all the procedure rules and hastily tries to disguise his fault. A letter from Kyiv regional
inspector, responsible for the protection of cultural monuments, to Ukrainian main department
of scientific institutions at the People’s Commissariat of Education gives the answers to many
questions. It clearly shows the attitude of the authorities and the residents of Baturyn to Fedir
Ernest and to the unauthorized opening of the Hetman`s crypt. There we find that the protocol
was drawn up later, all the procedure was not followed and the culprit took all relics from the
crypt and brought them to Konotop Museum. Fedir Ernest’s letter to Ukrainian main department
of scientific institutions at the People’s Commissariat of Education was published without any
abbreviations and with all of the linguistic and stylistic mistakes, inherent to that time. Spelling
errors are corrected without notifications.